Open-Access Infrared Spectra Depository for the Damage Assessment of Parchment - Charis Theodorakopoulos; Marianne Odlyha (Heritage)
An open-access infrared spectroscopy database of reference and historical parchments has been developed at Northumbria University in collaboration with Birkbeck, University of London. The resource includes the spectra acquired with attenuated total reflectance/Fourier transform infrared (ATR/FTIR) spectroscopy for a wide range of parchments, which were studied in the EU 5th Framework project “Improved Damage Assessment of Parchment” (IDAP). The parchment samples include reference samples, samples exposed to dry and humid heat, light, and inorganic gaseous pollutants, as well as parchments from three archives: Archivio di Stato di Firenze; the National Archives, Scotland; and the Royal Library and Royal Danish Academy—Architecture, Design, Conservation, Copenhagen. The database is invaluable for scholars, including archivists, conservation scientists, conservators, librarians, curators, and the general public, as to the best of our knowledge such a resource has not previously existed.